2019
DOI: 10.1016/j.redox.2019.101294
|View full text |Cite
|
Sign up to set email alerts
|

Redox responses in skeletal muscle following denervation

Abstract: Previous studies have shown a significant increase in the mitochondrial generation of hydrogen peroxide (H2O2) and other peroxides in recently denervated muscle fibers. The mechanisms for generation of these peroxides and how the muscle responds to these peroxides are not fully established. The aim of this work was to determine the effect of denervation on the muscle content of proteins that may contribute to mitochondrial peroxide release and the muscle responses to this generation. Denervation of the tibiali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
0
28
0
4
Order By: Relevance
“…The major finding of this study is that reduced expression of the superoxide scavenger CuZnSOD in neuronal tissue, initiated postdevelopment in adult mice, results in an early loss of alpha motor neurons in the ventral spinal cord, followed by a later disruption of neuromuscular junctions and muscle atrophy and weakness in the older mice. (Chipman, Schachner, & Rafuse, 2014;Scalabrin et al, 2019;Vasilaki et al, 2010). Thus, the second hit may involve the muscle reaching a threshold past which it no longer maintains NMJ structure and function allowing downstream effects of muscle mass and function to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The major finding of this study is that reduced expression of the superoxide scavenger CuZnSOD in neuronal tissue, initiated postdevelopment in adult mice, results in an early loss of alpha motor neurons in the ventral spinal cord, followed by a later disruption of neuromuscular junctions and muscle atrophy and weakness in the older mice. (Chipman, Schachner, & Rafuse, 2014;Scalabrin et al, 2019;Vasilaki et al, 2010). Thus, the second hit may involve the muscle reaching a threshold past which it no longer maintains NMJ structure and function allowing downstream effects of muscle mass and function to occur.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the HtrA2 mnd2(-/-) mice were sacrificed at 30 days postnatal. Considering the fact that mRNA levels, structure and weight of muscle did not significantly altered until 3-7 days after denervation [56][57][58][59][60][61], and that only 11% of specific force decrements are due to denervated fibers in rats [62], it suggests that the sarcopenia features observed in our study were not attributed to motor neurons degeneration. Consistent with our findings, Kang et al showed that HtrA2 mnd2(-/-) mice were rescued from neurodegeneration by transgenic expression of HtrA2/Omi in the brain, and adult transgenic HtrA2 mnd2(-/-) mice still developed accelerated aging phenotypes including muscle atrophy, indicating a role of HtrA2/Omi protease activity in muscle aging.…”
Section: Discussionmentioning
confidence: 76%
“…Transcripts of both PCG-1α and β, the regulators of mitochondrial proliferation, dramatically decrease after 24 h-denervation [ 237 ], suggesting early impairment of mitochondrial pool renewal. Monoamine oxidase A transcript and protein content was found to be increased between 3–24 h after denervation [ 87 , 244 ]. However, ROS production from mitochondria apparently increased later than 48-h denervation [ 103 , 104 , 244 ], possibly in concomitance with increased mitochondria misplacement at A band [ 245 ].…”
Section: Involvement Of Costamere Components In Different Muscle Amentioning
confidence: 99%
“…Monoamine oxidase A transcript and protein content was found to be increased between 3–24 h after denervation [ 87 , 244 ]. However, ROS production from mitochondria apparently increased later than 48-h denervation [ 103 , 104 , 244 ], possibly in concomitance with increased mitochondria misplacement at A band [ 245 ]. The possibility exists that other ROS sources do contribute to a very early increase in oxidative stress.…”
Section: Involvement Of Costamere Components In Different Muscle Amentioning
confidence: 99%